Electronics : a complete course - Cook, Nigel P., ....- (Upper Saddle River (N.J.) : Pearson/Prentice Hall, 2004)
Appropriate for DC/AC, DEVICES, DIGITAL Electronics courses in high schools, vocational-technical schools and community colleges. After 16 textbooks, 26 editions, and 19 years of front-line education experience, best selling author Nigel Cook's new text makes the world of electronics easily accessible in one complete text. Employing his now renowned student-friendly practical approach, this single text provides comprehensive coverage of the three electronics fundamental courses; DC/AC, DEVICES and DIGITAL.
Keywords: Elektronica